Edelman Revisited: Concepts, Achievements, and Challenges - Rohrscheib, Mark; Sam, Ramin; Raj, Dominic S.; Argyropoulos, Christos P.; Unruh, Mark L.; Lew, Susie Q.; Ing, Todd S.; Levin, Nathan W.; Tzamaloukas, Antonios H. (Frontiers in Medicine, 2022)
Many of the current approaches to both hyponatremia and hypernatremia are rooted in the 1958 study of Edelman. The key message from this study regarding management of dysnatremias states that combinations of external gains or losses of sodium, potassium and water leading to an increase of the fraction (total body sodium plus total body potassium) over total body water will raise the serum sodium concentration, while external gains or losses leading to a decrease in this fraction will lower the serum sodium concentration. A variety of studies have supported this concept and current quantitative methods for correcting dysnatremias are based on it. Newly described factors potentially affecting the concentration of sodium in serum water include the following: (a) exchanges during development or correction of dysnatremias between osmotically inactive sodium stored in tissues and osmotically active sodium in solution in body fluids; (b) the possibility of structured interfacial water which would decrease the amount of body water available for osmotic exchanges and ionic solvation; and (c) genetic influences on the determination of sodium concentration in body fluids. The effects of these newer developments on the methods of treatment of dysnatremias are not well established and will need extensive studying. Currently, monitoring of serum sodium concentration remains a critical step during treatment of dysnatremias.